1994
DOI: 10.1152/ajpheart.1994.267.1.h41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pregnancy on contraction and endothelium-mediated relaxation of renal and mesenteric arteries

Abstract: We have hypothesized that differences in the effect of pregnancy on mechanisms modulating vascular reactivity underlie the redistribution of cardiac output. Because pregnancy increases mesenteric blood flow by 75% and renal blood flow by only 10% in the guinea pig, we investigated the effect of pregnancy on vascular reactivity in these two beds. Relaxation in response to acetylcholine (ACh), an endothelium-dependent relaxing agent, and contraction induced by the thromboxane mimetic U-46619 were measured in rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
23
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 0 publications
4
23
1
Order By: Relevance
“…This is similar to the effect of pregnancy on the uterine, mesenteric and carotid arteries [12][13][14], Thus, the effect of pregnancy on stimulated NO release is specific for receptor-mediated release rather than for an alteration in the ability of the endothelium to produce NO or the sensi tivity of the underlying smooth muscle to NO.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This is similar to the effect of pregnancy on the uterine, mesenteric and carotid arteries [12][13][14], Thus, the effect of pregnancy on stimulated NO release is specific for receptor-mediated release rather than for an alteration in the ability of the endothelium to produce NO or the sensi tivity of the underlying smooth muscle to NO.…”
Section: Discussionsupporting
confidence: 53%
“…The mechanism by which pregnancy increases relax ation to ACh is apparently estradiol-dependent. Prior study has shown an increase in both basal and stimulated release of NO in some but not all vessel beds during preg nancy [12][13][14]. Calcium-dependent NO synthase activity is increased by pregnancy and these changes can be mim icked by estradiol administration and in the brain blocked by tamoxifen [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy is a physiological state where vasodilation is necessary to accommodate a 40-50% increase in blood volume required to meet the oxygen and nutritional requirements of the growing uterus and developing fetuses (18,43). This is accompanied by an attenuated responsiveness of maternal vessels to pressor agents (17,29,30,39,40,45) and an enhanced response to vasodilators (28,31). The mechanisms underlying these vascular changes are not clearly understood.…”
mentioning
confidence: 99%
“…High levels of circulating estrogen have been reported to modulate the vasoactive reagentsinduced responses. Acetylcholine (ACh)-induced endothelium-dependent vasodilations are increased during the late stage of pregnancy in guinea pig mesenteric artery (3) and rat aorta (4), and it has also been found in 17b-estradiol (E 2)-treated rat aorta (5) or rabbit femoral artery (6). Furthermore, we have reported that the relaxing response to isoprenaline (ISO) was suppressed by a short-term treatment with E2 in rat aorta (7).…”
mentioning
confidence: 99%